Короткі форми верлібру в сучасній українській і російській літературах - Кицан, Олена; Kytsan, Olena (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано короткі форми верлібру в сучасній українській і російській літературах. Об’єктом дослідження стали вільні вірші відомих сучасних поетів обсягом не більше п’яти рядків. Досліджується звʼязок верлібрових мініатюр зі східними жанрами, а саме хоку та танка. Адже сучасні верлібри, як і східні жанри тяжіють до лаконічності, мінімалістичності, філософічності, при цьому український та російський різновиди вільного вірша розвиваються своїми окремими шляхами. Показано спільне та відмінне між українським та російським вільним віршем, а також вектори їх руху.The article analyzes the short forms of vers libre in modern Ukrainian and Russian literatures. A free verse is a form of poetry that even through present causes most discussions among the scientists of verification. Though quite a lot new conceptions tend to appear, they are unable to grasp all the variety of verse libre forms. The free verses by a volume of no more than five lines became the object of the research. Connection of verses libre miniatures is investigated in its connection with east genres, namely haiku and tanka. The short unrhymed poetic texts in which the syllabic’s canons of the Japanese poetry are not observed interested us first of all, and also those texts in which the syllabic principles of hоku and tanka are reflected were generally reviewed. Attention was given to the connection of modern verse libres with east genres at the content level. As Ukrainian and especially Russian verse libres more often gravitate to the brevity, minimalism and philosophicity, the Ukrainian and Russian varieties of free verse develop the separate ways. Classification of a famous Russian scientist of versification Orlytskyi Y. that divides short vers libres into logical and vivid varieties was taken up as the basis. A common and different between the Ukrainian and Russian free verse, and also their movement vectors, are shown.
Short forms of vers libre in modern Ukrainian and Russian literatures
Keywords: верлібр; вільний вірш; література; поетика; жанр; хоку; танка; verse libre; free verse; verse; literature; poetics; genre; hоku; tanka